Cystatin C as a Predictor of Mortality and Cardiovascular Events in a Population with Chronic Kidney Disease - Ana Vigil; Emilia Condés; Luis Vigil; Paloma Gallar; Aniana Oliet; Olimpia Ortega; Isabel Rodriguez; Milagros Ortiz; Juan Carlos Herrero; Carmen Mon; Gabriela Cobo; Juana Jimenez (International Journal of Nephrology)
Background. We examine whether cystatin C, a surrogate marker of renal function, could identify patients with chronic kidney disease (CKD) with an increased risk of renal disease progression, death, or cardiovascular events. Methods. Data were obtained for 180 patients, with a diagnosis of chronic renal failure based on serum creatinine estimated glomerular filtration rate (eGFRcreat) <90 mL/min/1.73 m2. This population was grouped in tertiles according to cystatin C and creatinine values at baseline. Cardiovascular events and overall mortality were estimated for each tertile. Predictors of overall mortality and for the development of renal disease progression were analyzed. Results. The median age was 75 years (interquartile range 69–82) and the median eGFRcreat 38 mL/min m2 (interquartile range 33–49). Overall mortality was lower on the first and on the second tertiles of cystatin C than on the third one (HR = 0.060; 95% CI: 0.008–0.447 and HR = 0.094; 95% CI: 0.022–0.406, resp.). Deaths related to the creatinine tertiles followed the same pattern, but differences were not as large. Cardiovascular mortality was lower on the second than on the third cystatin C tertile (HR = 0.198; 95% CI: 0.040–0.987), but it did not show differences on the first and the second creatinine tertiles compared with the third one (HR = 0.126; 95% CI: 0.013–1.265 and HR = 0.403; 95% CI: 0.093–1.740). The only independent predictors of mortality during followup were baseline cystatin C (OR = 0.100; 95% CI: 0.021–0.463) and baseline uric acid (OR = 1.377; 95% CI: 1.070–1.773). Conclusion. Cystatin C may be an alternative to creatinine for detecting a high risk of death and cardiovascular events in a population with CKD.